2010
DOI: 10.1182/blood-2009-10-248872
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of proapoptotic Puma selectively protects hematopoietic stem and progenitor cells against high-dose radiation

Abstract: Bone marrow injury is a major adverse side effect of radiation and chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 33 publications
8
68
1
Order By: Relevance
“…27 In response to DNA damage (e.g., γ-irradiation) and cytokine withdrawal, PUMA appears to be more important than NOXA for apoptosis of normal hematopoietic stem and progenitor cells. [30][31][32][33][34] Here, we provide the first evidence of a similar predominant role for PUMA in oncogene-induced apoptosis of hematopoietic stem and progenitor cells in vivo. Interestingly, the absence of PUMA but not loss of p53 rescued myeloid progenitors, suggesting that the mechanism of apoptosis is not a simple linear pathway from p53 to PUMA.…”
Section: Discussionmentioning
confidence: 58%
“…27 In response to DNA damage (e.g., γ-irradiation) and cytokine withdrawal, PUMA appears to be more important than NOXA for apoptosis of normal hematopoietic stem and progenitor cells. [30][31][32][33][34] Here, we provide the first evidence of a similar predominant role for PUMA in oncogene-induced apoptosis of hematopoietic stem and progenitor cells in vivo. Interestingly, the absence of PUMA but not loss of p53 rescued myeloid progenitors, suggesting that the mechanism of apoptosis is not a simple linear pathway from p53 to PUMA.…”
Section: Discussionmentioning
confidence: 58%
“…More recently, several groups of investigators reported that Puma, a downstream target of p53 and a proapoptotic BH3-only protein, plays a critical role in mediating IR-induced HSC apoptosis and ARS (140,172). They showed that Puma was selectively induced by IR in LSK cells and LSK cells from Puma knockout mice were insensitive to IR-induced apoptosis.…”
Section: Ir-induced Apoptosis In Hscsmentioning
confidence: 99%
“…However, very recent studies provide surprising new information on the role of PUMA in certain cancer types, emphasizing the "dark side" of the function of this proapoptotic molecule. Surprisingly, it turns out that genetic ablation of PUMA paradoxically leads to a protective effect for hematopoietic stem/progenitor cells (HSPCs) against γ radiation and the induction of mutations in these cells [104,105]. This inhibits the development of lymphomas [106,107] and hepatocellular carcinoma under certain conditions [108].…”
Section: Puma In Carcinogenesismentioning
confidence: 99%